207 A high genetic risk score is associated with early disease onset, organ damage and decreased survival in systemic lupus erythematosus. (April 2019) - Reid, Sarah; Alexsson, Andrei; Frodlund, Martina; Sandling, Johanna; Bolin, Karin; Svenungsson, Elisabet; Jönsen, Andreas; Bengtsson, Christine; Gunnarsson, Iva; Bengtsson, Anders A; Rantapää-Dahlqvist, Solbritt; Eloranta, Maija-Leena; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic, autoimmune disease with a complex genetic etiology. Over 100 risk genes for SLE have been identified at genome-wide significance, but their overall effect on disease severity has not previously been studied. We therefore assessed the relationship between a high genetic risk score and the development of organ damage in SLE. Methods: Patients with SLE, who met 4 ACR criteria (n=1001), and healthy controls (n=2802) were genotyped using a 200K Immunochip SNP Array (Illumina). A genetic risk score (GRS) was assigned to each individual based on 57 SLE risk loci which have previously shown association (p<5×10–8) with SLE according to Chen et al (Curr Opin Rheumatol, 2017; 29(5):423–433), weighted by their SLE susceptibility odds ratios (ORs). Clinical data was retrieved from medical charts. Results: SLE prevalence increased with increasing GRS (figure 1 A) and was higher in the highest compared to the lowest GRS-quartile (OR 12.32 (9.5315.71) p=7.9×10–86). SLE onset occurred 5 years earlier in the high compared to the low quartile (figure 1 B). The OR for organ damage increased with increasing GRS (figure 1 C) and was significantly higher in the high compared to the low GRS-quartile (OR 1.47 (1.062.04) p=2.0×10–2). Moreover, patients in the high quartile had an increased prevalence of nephritis (OR 2.22 (1.503.27), p=5.9×10–5), end-stage kidney disease (ESKD) (OR 5.58 (1.5020.79), p=1.0×10–2) anti-dsDNA antibodies (OR 1.83 (1.192.81), p=6.1×10–03), anti-cardiolipin-IgG (OR 2.16 (1.303.59), p=2.8×10–03) and anti-2-glycoprotein-I (OR 1.69 (1.042.74), p=3.3×10–02). Analysis of renal biopsy data showed that the prevalence of proliferative nephritis was significantly higher in the high, compared to the low, quartile (OR 2.42 (1.304.49), p=5.1×10–03). Moreover, the patients in the high GRS-quartile displayed decreased survival until their first organ damage (HR 1.51 (1.042.25), p=3.7×10–02), first cardiovascular event (HR 1.65 (1.032.64), p=2.6×10–02), nephritis onset (HR 2.53 (1.723.71) p=9.6×10–7) and ESKD (6.78 (1.7826.86), p=6.5×10–3). Lastly, OR for mortality increased with increasing GRS (figure 1 D), with a 5 year decrease in overall survival in the high compared to the low quartile (HR 1.82 (1.043.19), p=2.4×10–2). Conclusions: A high genetic risk score is associated with earlier disease onset, increased risk of organ damage and impaired survival. Our results indicate that genetic profiling may be useful for predicting outcomes in patients with SLE. Funding Source(s): None